QbD-Driven Hydrotropic UV Method for Simultaneous Quantitation of Poorly Soluble Drugs, Irbesartan and Hydrochlorothiazide in Bulk and Tablet Formulation - Susmitha, Aggarapu; Rajitha, Galla (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Developing a reliable and precise method for the simultaneous quantitation of poorly soluble drugs, Irbesartan (IRB) and Hydrochlorothiazide (HCTZ), in bulk and formulations poses significant challenges due to their poor aqueous solubility and low proportional ratio. A robust, sustainable, and AQbD-driven UV spectrophotometric approach is essential to overcome these limitations and ensure accurate quantification. Materials and Methods: A hydrotropic solubility enhancement technique was employed using sodium bicarbonate as the optimal hydrotrope. Systematic AQbD principles guided the selection and optimization of concentration (1M) and volume (5 mL) of hydrotrope to maximize solubility without compromising the UV spectroscopic signal. IRB and HCTZ exhibited absorption maxima at 231 nm and 272 nm, respectively. Results: The optimized method obeyed Beer’s law in the concentration ranges of 5.0-30.0 mcg/mL for IRB and 0.75-2.50 mcg/mL for HCTZ. The optimum concentrations of IRB and HCTZ were 15 μg/mL and 1.25 μg/mL, with absorbance values of 0.539 and 0.418, respectively. Excellent linearity with regression coefficients of 0.9997 for IRB and 0.9991 for HCTZ, no interference from pharmaceutical excipients was observed. The method was validated according to ICH guidelines and successfully applied for routine analysis of IRB and HCTZ in bulk and formulations. Conclusion: This sustainable AQbD-driven approach simplifies the analysis of poorly soluble drugs. The method can be successfully used for the quality control of these drugs in fixed dose combination.
Keywords: Quality by design; Irbesartan; Hydrochlorothiazide; Hydrotropy; UV spectroscopy